2018
DOI: 10.1186/s12889-018-5238-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of depression and anxiety with cardiovascular co-morbidity in a primary care population in Latvia: a cross-sectional study

Abstract: BackgroundCardiovascular (CV) diseases (CVDs) are the leading cause of mortality worldwide. Globally, there is a growing interest in understanding and addressing modifiable psychosocial risk factors, particularly depression and anxiety, to prevent CVDs and to reduce morbidity and mortality. Despite the high premature mortality rate from CVDs in Latvia, this is the first Latvian study to examine the association of depression and anxiety with CVD morbidity in a primary care population.MethodsThis cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 67 publications
1
11
0
2
Order By: Relevance
“…Furthermore, PHQ -9 and GAD-7 appears to be a reliable and valid instrument that can be used to diagnose major depression (18.5%) and anxiety (15.2%) among Turkish women. This is consistent the with prevalence rate of major depression and anxiety observed rates 15.4% and 14.4% in United States among women (Elrashidi et al, 2018), also similarly study reported for the depression 14.7%, and anxiety 10.1% conducted in Latvia women (Ivanovs et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, PHQ -9 and GAD-7 appears to be a reliable and valid instrument that can be used to diagnose major depression (18.5%) and anxiety (15.2%) among Turkish women. This is consistent the with prevalence rate of major depression and anxiety observed rates 15.4% and 14.4% in United States among women (Elrashidi et al, 2018), also similarly study reported for the depression 14.7%, and anxiety 10.1% conducted in Latvia women (Ivanovs et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Cardio- and cerebrovascular disorders are recognized worldwide as the most frequent causes for death and major depressive disorder (MDD) for disability [ 1 ]. In recent cross-sectional studies, repeatedly an association of current depressive symptoms and lifetime depressive episodes with cardiovascular disease (CVD), could be confirmed [ 2 ]. MDD represents a major risk factor for CVD and for myocardial infarction (MI) [ 3 ] independent of traditional risk factors [ 4 ], this seems to be especially true in geriatric depression [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of elevated symptoms of anxiety in CV patients has been reported to be approximately 30% ( 12 , 14 ). Data on the relationship between depression, anxiety and CVD from the Baltic region are limited and controversial ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%